Cambridge Idioms Dictionary - McCarthy M. Michael (Cambridge, Cambridge University Press, 2006)
This new edition of the Cambridge Idioms Dictionary explains over 7,000 idioms current in British, American and Australian English, helping learners to understand them and use them with confidence. Fully updated with new idioms, e.g. think outside the box, play out of your skin, the new black New, attractive page layout with idioms in colour for easy reference Clear explanations and example sentences for every idiom Most common idioms highlighted so students know which to learn Topic section covering useful language areas, e.g. agreeing and disagreeing, telling stories